Long-Lasting Effects of the 2013 Yolanda Typhoon on Overall Health of Mothers and Children. (27th June 2021) - Horiguchi, Hanna; Nakazawa, Minato
ABSTRACT: Objectives: Three years after the 2013 Yolanda Typhoon, this study sought to determine the factors associated with the stress of the affected mothers and the health of the children on Leyte island, and the preparedness of the community to mitigate future potential disasters. Methods: Three hundred mothers with children from 0 to 7 years old were selected through convenience sampling, structured interviews conducted using the Hurricane-Related Traumatic Experiences questionnaire and the PTSD (post-traumatic stress disorder) Checklist 5 (PCL5), and the children's weights and heights were measured. Results: The provisional PTSD prevalence was found to be 53.3% 3 y after Yolanda. The multiple regression analysis with multiple imputation for the missing values found that housing and childcare attitudes were significantly associated with preparedness. Conclusions: This study concluded that living in multistoried houses was useful for disaster mitigation and that the caregiving responsibility for their children could be a disaster preparedness motivation for mothers.